(untitled) (London Journal of Medical and Health Research, 2025)
This case study explores a rare presentation of tokophobiaan intense, pathological fear of childbirthin a 38-year-old Togolese woman named Afi, situated within a highly pro-natalist cultural context. Unlike the normative expectations in Togo, where motherhood is celebrated and socially reinforced from an early age, Yawadeveloped a persistent fear of pregnancy and childbirth following early developmental trauma and using an integrative therapeutic approachincluding cognitive-behavioral therapy, imagery desensitization, psychoeducation, and observational exposurethe intervention aimed to reframe traumatic associations and restore autonomy in reproductive decision-making. The treatment was framed within a solution-focused and brief therapy model and culturally adapted to fit collective values. The findings underscore the importance of trauma-informed, culturally sensitive interventions in underrecognized mental health conditions such as tokophobia, particularly in African contexts where such cases are seldom documented. While the results are not generalizable, this case contributes to the emerging literature on reproductive trauma in non-Western settings.